The influence of vegetation and soil properties on springtail communities in a diesel-contaminated soil - Errington, Ingrid; King, Catherine K.; Houlahan, Sarah; George, Simon C.; Michie, Alexander; Hose, Grant C. (Science of The Total Environment, 2018)
Soil health is important for the functioning of all terrestrial ecosystems, but may be impacted by contamination. Soil contamination may in turn necessitate rehabilitation and remediation works, but many of the techniques currently used cause physical disturbance to the soil structure, which may in itself affect soil assemblages. An understanding of the relative influence of these two types of disturbance on soil biota is needed to inform in situ remediation activities. Subantarctic Macquarie Island provides an ideal location to study these interactions because soil biodiversity is naturally low and a number of diesel spills have undergone active in situ remediation in recent years. In this study, soil cores were collected in triplicate from 21 locations. Springtails were extracted and identified to genus/species level. Total petroleum hydrocarbon (TPH) concentrations were measured at the surface and at 0.5 m depth at each site, as was vegetation coverage and a range of soil properties. The relationships between these data were examined using distance-based linear models. Together, all environmental variables (vegetation and soil properties) explained a total of 76% of the variation in springtail assemblages. Soil properties alone accounted for 52% of the variation in springtail assemblages, of which bulk density was most important followed by soil conductivity and pH. Vegetation cover by the four plant taxa accounted for 34% of variation observed, with Leptinella plumosa and Poa foliosa having the greatest influence. Surface and underlying TPH concentration did not have a significant effect on springtail assemblages. Overall, factors that can be linked to physical soil disturbance had greater influence over springtail assemblages than did soil contamination. This finding may influence the selection of the most appropriate contaminant management approach for environmentally sensitive sites.